A new species of Aspidimorpha (Coleoptera: Chrysomelidae: Cassidinae: Aspidimorphini) from Uganda - Borowiec, Lech; Sekerka, Lukáš (Zootaxa, 2014)
Aspidimorpha (Aspidimorpha) wagneri sp. nov. is described from Uganda. This species belongs to the nominotypical subgenus, together with several African species that are closely related to A. mutata Boheman, 1854. Its relative position within the genus is discussed.